Incidence of multiple myeloma in Kailuan cohort: A prospective community-based study in China. (June 2022) - Gao, Wen; Zheng, Yurong; Zhang, Runhua; Liu, Gaifen; Jian, Yuan; Zhou, Huixing; Zhang, Zhiyao; Chen, Shuohua; Wu, Shouling; Chen, Wenming
Abstract: Background: Previous retrospective studies showed that the incidence and mortality rates for MM in China were lower than those in western countries. A large-scale prospective study on incidence and mortality rates of MM is still lacking. Methods: Based on the prospective Kailuan Cohort study in China, we included all patients with MM in Kailuan Cohort from June 1, 2008 to December 31, 2016. Using the numbers of diagnosed cases and deaths during the study period as the numerators and the corresponding observed person-years as the denominators respectively, we calculated crude incidence and mortality rates. The 95% confidence intervals for crude incidence rate and mortality rate were estimated base on Poisson distribution. Rates were standardized by direct standardization according to the China population in 2000 and Segi' world standard population. Results: A total of 22 members from Kailuan Cohort were first diagnosed with MM between 2008 and 2016. The calculated crude incidence rates were 2.8 (95% CI, 1.7–4.2) per 100, 000 person-years for all participants. The standardized incidence rate was 0.9 per 100, 000 person-years (95% CI, 0.5–2.1) when standardized by 2000 China population census data, and 1.0 per 100, 000 person-years (95% CI, 0.6–1.8) when standardized by Segi's world standard population (WSP). The calculated crude mortality rates were 2.3 (95% CI, 1.4–3.6) per 100, 000 person-years. The mortality standardized by 2000 China population census data was 0.7 per 100, 000 person-years (95% CI, 0.3–1.9), and 0.9 per 100, 000 population (95% CI, 0.5–1.7) when standardized by Segi's WSP. Both incidence and mortality for males were higher than that for females almost in all age groups. Both rates increased steadily with age. Conclusion: In this community-based prospective cohort study, we found that the incidence of MM in China was far lower than that in American and Europe. Highlights: Few population-based studies have been conducted to assess the incidence of Multiple myeloma (MM) in China. Previous retrospective studies showed that the incidence for MM in China were lower than those in western countries. Based on the prospective Kailuan Cohort study, the crude incidence were 2.8 (95% CI, 1.7–4.2) per 100, 000 person-years.